An African swine fever virus gene with homology to DNA ligases. - Hammond, J M (1992)
Sequence analysis of the SalI g region of the genome of a virulent isolate of ASFV (Malawi Lil 20/1) has revealed an open reading frame with the potential to encode a 48 kilodalton (kD) polypeptide which has significant homology with eukaryotic and prokaryotic DNA ligases. This ASFV encoded gene also contains the putative active site region of DNA ligases including the lysine residue which is necessary for enzyme-adenylate adduct formation, but lacks the C-terminal basic region conserved in other eukaryotic DNA ligases. A novel [32P]-labelled potential DNA ligase-adenylate adduct of M(r) 45 kD was observed upon incubation of ASFV infected cell cytoplasmic extracts with alpha-[32P]-ATP and subsequent analysis of products by SDS/PAGE. These data together suggest that ASFV encodes its own DNA ligase.